2016
DOI: 10.1111/srt.12326
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional 3D mapping of skin tumours with non‐invasive multispectral optoacoustic tomography

Abstract: Our findings confirm the potential benefit of the new imaging method in guiding surgical intervention to achieve a more precise excision with better clearance and lower relapse rates. It can also potentially help to shorten the duration of Mohs' micrographic surgery. Further large-scale studies are necessary to ensure correlation between MSOT and histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…They were able to successfully use PAI to detect the tumor depth in vivo till a depth of 3.75mm in nude mice. In a later study of Chuah et al [85] similar results were found when they performed PAI measurements on three patients with skins tumors. They used PAI to acquire a 3D image of the skin tumors and compared those measurements with histological measurements.…”
Section: Clinical Application Of Paisupporting
confidence: 62%
“…They were able to successfully use PAI to detect the tumor depth in vivo till a depth of 3.75mm in nude mice. In a later study of Chuah et al [85] similar results were found when they performed PAI measurements on three patients with skins tumors. They used PAI to acquire a 3D image of the skin tumors and compared those measurements with histological measurements.…”
Section: Clinical Application Of Paisupporting
confidence: 62%
“…Multispectral optoacoustic tomography is a noninvasive imaging tool that can map skin tumors via optical contrast with accuracy comparable to histologic measurements. 5 3-Dimensional facial imaging and printing can be used to calculate tumor surface area for customized masks, leaving sufficient skin for excision and reconstruction. Patient face coverings would cover the nose and mouth, only expose relevant areas near the excision site, and include adjustable/removable ear loops for tumors localized to the ears.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Both the jacket and holder were designed using the computer-aided design (CAD) software package SolidWorks 2015 (Dassault Systemes S.A., Waltham, MA, USA) and fabricated using a 3-D printer (ProJet 3500, 3D Systems, Inc., Rock Hill, SC, USA) with an accuracy of 0.016 mm. The incident angle of the fiber was optimized to 41 • using the method from a previous study [17] to achieve coplanar light delivery and acoustic detection. The incident energy density on the imaging sample surface was estimated to be approximately 12 mJ/cm 2 , which is much lower than the American National Standards Institute (ANSI) safety limit (20 mJ/cm 2 ) [18].…”
Section: Design Of the Photoacoustic Probe-integration Of The Fiber Bmentioning
confidence: 99%